The Implementation of Multicultural Education and Extra-Curricular Activities at Pesantren - Rahman, Bambang Arif (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2019)
AbstractThis study aims to investigate how pesantren (Islamic boarding schools) conducts extra-curricular activities (ECAs) and how pesantren promotes multicultural education for students through ECAs Pesantren is portrayed as an exclusive educational institution that creates a generation of radical and intolerant Muslims. However, this study describes how one pesantren in Indonesia has carried out and substantially supported the implementation of multicultural education among students through ECAs. The pesantren has made a valuable effort to promote the recognition, understanding, and awareness of Indonesian SARA (Suku, Agama, Ras, Antar-golongan/ethnic, religious, racial, and inter-groups) issues. This qualitative study involved in-depth interviews with Kyai (top leader/principal), ECA teachers, and students. The study also observed the various ECAs at Pesantren Assalaam, and students completed a questionnaire. Pesantren Assalaam structures its ECAs to instil knowledge of, provide a supportive environment for, and help students experience the cultural diversity of the country. The school focuses on awareness of the relationship among various ethnicities, religions, and local cultures. Students are inculcated with the fundamental values of multicultural education, such as tolerance, respect, togetherness, and appreciation. This study proposes a model of multicultural education implementation for pesantren.AbstrakPenelitian ini bertujuan untuk menyelidiki bagaimana pesantren melakukan kegiatan ekstra kurikuler (ECA) dan bagaimana pesantren mempromosikan pendidikan multikultural untuk siswa melalui ECA. Pesantren digambarkan sebagai lembaga pendidikan eksklusif yang menciptakan generasi Muslim radikal dan tidak toleran. Namun, penelitian ini menggambarkan bagaimana satu pesantren di Indonesia telah melaksanakan dan secara substansial mendukung implementasi pendidikan multikultural di kalangan siswa melalui ECA. Pesantren telah melakukan upaya yang berharga untuk mempromosikan pengakuan, pemahaman, dan kesadaran SARA Indonesia (Suku, Agama, Ras, Antar-golongan / etnis, agama, ras, dan antar kelompok). Studi kualitatif ini melibatkan wawancara mendalam dengan Kyai (pemimpin puncak/kepala sekolah), guru ECA, dan siswa. Studi ini juga mengamati berbagai ECA di Pesantren Assalaam, dan siswa menyelesaikan kuesioner. Pesantren Assalaam menyusun ECA-nya untuk menanamkan pengetahuan tentang, menyediakan lingkungan yang mendukung, dan membantu siswa mengalami keanekaragaman budaya negara. Sekolah ini berfokus pada kesadaran akan hubungan antara berbagai etnis, agama, dan budaya lokal. Siswa ditanamkan dengan nilai-nilai dasar pendidikan multikultural, seperti toleransi, rasa hormat, kebersamaan, dan penghargaan. Studi ini mengusulkan model implementasi pendidikan multikultural untuk pesantren. How to Cite: Rahman, B. A. (2019). The Implementation of Multicultural Education and Extra-Curricular Activities at Pesantren. TARBIYA: Journal of Education in Muslim Society, 6(2), 117-133. doi:10.15408/tjems.v6i2. 11915.